Remote monitoring of solar PV system for rural areas using GSM, V-F & F-V converters. (3rd May 2016) - Tejwani, R.; Kumar, G.; Solanki, C.S.
Abstract: The Small capacity photovoltaic (PV) systems like solar lantern and home lighting systems installed in remote rural area often fail without any prior warning due to lack of monitoring and maintenance. This paper describes implementation of remote monitoring for small capacity solar PV system that uses GSM voice channel for communication. Through GSM analog signal of sine wave with frequency range 300–3500 Hz and amplitude range 2.5–4 V is transmitted. Receiver is designed to work in the same frequency range. The voltage from solar PV system in range of 2 to 7.5 V can be converted to frequency directly at the transmitting end. The frequency range from 300–6000 Hz can be sensed and directly converted to voltage signal at receiving end. Testing of transmission and reception of analog signal through GSM voice channel is done for voltage to frequency (V-F) and frequency to voltage (F-V) conversions.